Mobile TV: Customizing Content and Experience - Marcus, Aaron; Roibás, Anxo Cereijo; Sala, Riccardo (Human-Computer Interaction Series, 2010)
Mobile TV: Customizing Content and Experience documents current research and case studies of design practice that seek to improve the mobile television experience. Developing usable, useful, and appealing solutions for the customer or user experience, i.e., successful products and services, requires customization according to specific users' needs amidst frequently changing physical and social environments. Complex design problems like these require interdisciplinary perspectives that cover software functionality, human interaction and communication experiences, and perceived value. Contributors from academia, business, and design have contributed their collective expertise and experience to deliver wisdom on all fronts. Divided into seven parts, the book's first chapter establishes definitions and summarizes current research and development. The subsequent chapters specifically look at Mobile TV experience in everyday life, innovative conceptual and participatory design methods, contextual analysis methods, social context for interactive multimedia systems, advanced interaction with mobile digital content, and future trends for the wide range of products and services that will be offered in the decade to come. A balance between theoretical and empirical approaches provides insight into principles and methods, as well as actionable guidelines and recommendations for all those interested in exploring how to achieve the core objectives of usability, usefulness, and social appeal of this new mobile-video technology. The book answers many questions, but also raises some new ones that only future technology development and deployment in mobile human-computer interaction and communication can answer.